Economics of Adoption of Environmental Sustainable Fishing Techniques in Coastal Mangrove Niger Delta, Nigeria - Ehirim, N. C.; Praise, N. C.; Osuji, E. E.; Onyemauwa, S. C. (Archives of Business Research, 2018)
Reduction in social benefits in form of fishery stock depletion has some fishing techniques seriously fingered as low economic performance among fisher folks is leading to low revenue and unemployment in Mangrove Swamp Zone (MSZ) of Nigeria. Data were obtained from a two-stage sampling technique from 206 artisanal fishermen in two states within MSZ. Data on fisher folks’ socioeconomic features, adoption level of environmental sustainable fishing techniques (ESFT), quantity and unit selling prices of species of catch as well as inputs were elicited using a well-structured questionnaire and analyzed using both descriptive and budgetary tools. Majority (68.9% and 64.2%) of fishing activities are done with dugout canoes with only a few (16.0% and 16.7%) motorized vessels that goes further off-shore in Bayelsa and Rivers State respectively. Adption level of ESFT of 26.1% and 24.1% for Bayelsa and River State respectively is low. Nematopalaemon hastatis recorded the highest (46.6%) returns of USD 345.77/fisherman, as fleet dominated sea-shore for it. Though artisanal fishing in MSZ seems economically sustainable with benefit-cost across different adopters greater than unity and rate of returns to investment ratio of 1.37, ranging from 1.33 in Rivers to 1.44 in Bayelsa State, but poses a high marginal social cost to the breeding areas as catch is very concentrated at the sea shore of less than 5nm. There is a low catch of some pelagic species (Etamopterus penyl). The study recommends a persuasive extension demonstartion, litigation and the use water poilce to enforce strict adherence to principles ESFT for sustainable artisanal fishing activities in the mangrove region of Niger Delta.